2006
DOI: 10.1007/s11103-006-0029-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Novel O-methyltransferases from the Vanilla planifolia Caffeic Acid O-methyltransferase

Abstract: The biosynthesis of many plant secondary compounds involves the methylation of one or more hydroxyl groups, catalyzed by O-methyltransferases (OMTs). Here, we report the characterization of two OMTs, Van OMT-2 and Van OMT-3, from the orchid Vanilla planifolia Andrews. These enzymes catalyze the methylation of a single outer hydroxyl group in substrates possessing a 1,2,3-trihydroxybenzene moiety, such as methyl gallate and myricetin. This is a substrate requirement not previously reported for any OMTs. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
(59 reference statements)
0
30
0
Order By: Relevance
“…Although they can have varied and multiple substrates class II OMTs are still commonly referred to as caffeic acid OMTs as early studies on lignin biosynthesis focused on their ability to methylate this substrate Gowri et al 1991). As well as acting on the lignin precursors caffeic acid and 5-hydroxyferulic acid, class II OMTs have been shown to be involved in the synthesis of a diverse range of secondary metabolites including flavonoids, flavonols, stilbenes, phenylpropenes and various volatile phenolics (Akashi et al 2003;Lavid et al 2002;Li et al 2006;Schmidlin et al 2008;Wein et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although they can have varied and multiple substrates class II OMTs are still commonly referred to as caffeic acid OMTs as early studies on lignin biosynthesis focused on their ability to methylate this substrate Gowri et al 1991). As well as acting on the lignin precursors caffeic acid and 5-hydroxyferulic acid, class II OMTs have been shown to be involved in the synthesis of a diverse range of secondary metabolites including flavonoids, flavonols, stilbenes, phenylpropenes and various volatile phenolics (Akashi et al 2003;Lavid et al 2002;Li et al 2006;Schmidlin et al 2008;Wein et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Progress in cloning of OMTs and the advent of first crystal structures (Zubieta et al, 2001(Zubieta et al, , 2002Gang et al, 2002) revealed that OMTs may have subtle structure-function relationships and are substrate specific. Recently, the evolution of defined substrate requirements was demonstrated for compounds in the scent of V. planifolia (Li et al, 2006). BX7 may represent an OMT with a narrow substrate spectrum.…”
Section: Discussion All Genes Of Benzoxazinone Biosynthesis In Maize mentioning
confidence: 99%
“…for Vanilla planifolia and Rosa spp. OMTs (Scalliet et al, 2002;Li et al, 2006). The pH optimum for the reaction is at 7.0; pH optima of 7 to 8 are often displayed by OMTs (Gang et al, 2002;Lavid et al, 2002).…”
mentioning
confidence: 99%
“…We have been using an in vitro activity approach to screen candidate OMT genes that encode proteins with such an activity (Pak et al 2004;Li et al 2006). In this study, we generated a cDNA library from the hair cells in developing V. planifolia pods and identified and characterized two cDNAs that encode novel Class I OMTs.…”
Section: Introductionmentioning
confidence: 99%